Water, sanitation, handwashing, and nutritional interventions can reduce child antibiotic use: evidence from Bangladesh and Kenya - Ayse Ercumen; Andrew N. Mertens; Zachary Butzin-Dozier; Da Kyung Jung; Shahjahan Ali; Beryl S. Achando; Gouthami Rao; Caitlin Hemlock; Amy J. Pickering; Christine P. Stewart; Sophia T. Tan; Jessica A. Grembi; et al. (Nature Communications)
Abstract Antibiotics can trigger antimicrobial resistance and microbiome alterations. Reducing pathogen exposure and undernutrition can reduce infections and antibiotic use. We assess effects of water, sanitation, handwashing (WSH) and nutrition interventions on caregiver-reported antibiotic use in Bangladesh and Kenya, longitudinally measured at three timepoints among birth cohorts (ages 3–28 months) in a cluster-randomized trial. Over 50% of children used antibiotics at least once in the 90 days preceding data collection. In Bangladesh, the prevalence of antibiotic use was 10–14% lower in groups receiving WSH (prevalence ratio [PR] = 0.90 (0.82–0.99)), nutrition (PR = 0.86 (0.78–0.94)), and nutrition+WSH (PR = 0.86 (0.79–0.93)) interventions. The prevalence of using antibiotics multiple times was 26–35% lower in intervention arms. Reductions were largest when the birth cohort was younger. In Kenya, interventions did not affect antibiotic use. In this work, we show that improving WSH and nutrition can reduce antibiotic use. Studies should assess whether such reductions translate to reduced antimicrobial resistance.